Relictos de bosques y su efecto en la conservación de mamíferos terrestres en la región tumbesina ecuatoriana. período 2018 - 2019 - Centeno Morales, Víctor Alfonso (2020)
In the coastal region of the province of Manabí, we find remnants of dried tropical forests that have barely been studied, which are outside of the system of protected areas and house a big community of mammals. Within the months of January, February, and March of 2018, and February, March, April, June, July, and September of 2019, four hidden cameras were installed in the region of the Ecuadorian Tumbesina with the purpose of examining the abundance and richness of mammals and generating maps of the mentioned zones through georeferencing. The cameras identified 18 species from which three are endangered, one threatened according to the red book of mammals of Ecuador, and two almost endangered according to the criteria of the International Union of Conservation of Nature (IUCN). The most abundant species were the common opossum (Didelphis marsupialis), the lowland paca (Cuniculus paca), the crab-eating raccoon (Procyon cancriverous), and the Sechuran fox (Pseudalopex sechurae). The least abundant species were the greater grison (Galictis vittata), the red-tailed squirrel (Notosciurus granatensis), and the margay (Leopardus wiedii). This information can be useful for the creation of conservation and management programs for large and medium sized mammals of the Ecuadorian Tumbesina region, specifically for species cataloged at a national threat level. Key word Camera traps, wild fauna, mammals, remnants of forest, Tumbes region